Stand dynamics and tree quality response to precommercial thinning in a northern hardwood forest of the Acadian forest region: 23 years of intermediate results. Issue 1 (2nd January 2017) - Swift, D. Edwin; Knight, William; Béland, Martin; Boureima, Issifi; Bourque, Charles P.-A.; Meng, Fan-Rui
ABSTRACT: In the late 1980s, large forest companies began precommercial thinning (PCT) operations in young northern hardwood cutovers in New Brunswick, Canada. To provide supporting growth and yield information, an industrial experiment was established at residual stand densities of 1300, 1600, 1900, and 2200 stems ha −1 . Stand responses were examined for measurements recorded at 0 (1987), 5 (1992), 10 (1997), 16 (2003), and 23 (2010) years after establishment. Average diameter at breast height, quadratic mean diameter, stand basal area, and stand total volume growth increased as stem density decreased from PCT. There were significant linear differences for many of these variables between treatments and time periods (year). No significant differences were detected in tree height between treatments. In 2010, the four PCT thinning treatments did not exhibit any differences in potential sawlogs at 2.4 m (8 ft) and 3.6 m (12 ft) lengths. Significant differences were observed for 4.9 m (16 ft) sawlogs that were produced at the least dense spacing (1300 stems ha −1 ). Results from this study and recommendations from the European literature suggest that value-added timber products may be produced from more intense PCT treatments than are currently being practiced on sites dominated by yellow birch ( Betula alleghaniensis Britt.).